2008
DOI: 10.1099/vir.0.2008/000166-0
|View full text |Cite
|
Sign up to set email alerts
|

The promiscuous evolutionary history of the family Bromoviridae

Abstract: Recombination and segment reassortment are important contributors to the standing genetic variation of RNA viruses and are often involved in the genesis of new, emerging viruses. This study explored the role played by these two processes in the evolutionary radiation of the plant virus family Bromoviridae. The evolutionary history of this family has been explored previously using standard molecular phylogenetic methods, but incongruences have been found among the trees inferred from different gene sequences. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 58 publications
1
24
1
1
Order By: Relevance
“…Another is to aim not for a single, bifurcating phylogenetic tree, but a network (Huson & Bryant 2006). The blended evolutionary history of several plant viruses has been traced using split network methods in SPLITSTREES4 (Hu et al 2007;Codoner & Elena 2008;Martin et al 2009). While networks can better reflect the true ancestry of many recombinant plant viruses, the analysis of migration and hypothesis testing is more complicated on a network than bifurcating trees (Huson & Bryant 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Another is to aim not for a single, bifurcating phylogenetic tree, but a network (Huson & Bryant 2006). The blended evolutionary history of several plant viruses has been traced using split network methods in SPLITSTREES4 (Hu et al 2007;Codoner & Elena 2008;Martin et al 2009). While networks can better reflect the true ancestry of many recombinant plant viruses, the analysis of migration and hypothesis testing is more complicated on a network than bifurcating trees (Huson & Bryant 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Mixed infections provide an opportunity for recombination and reassortment of genetic material from multipartite viruses (Pressing & Reanney, 1984;Roossinck, 1997). Genetic exchange occurs with other Bromoviridae members (Codoñer & Elena, 2008) to potentially result in new species which may have quite different host range and pathogenicity characteristics. It is unclear if our observations of mixed RNA segments from TSV-parthenium and TSV-crownbeard indicate these strains are capable of complementing each other or if a new hybrid strain could arise from a reassortment of RNA segments.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, whereas information on recombination in PPV made available by various researchers (Cervera et al 1993;Glasa et al 2004Glasa et al , 2005Matic et al 2006;Salvador et al 2006) remains limited, knowledge on recombination in the CP gene of ACLSV, PDV, ApMV, and PNRSV is still lacking. It should be noted that recently Codoner and Elena (2008) reported that based on RNA-2 sequence analysis, PDV and PNRSV seem to be the potential minor and major parents, respectively, of Alfalfa mosaic virus (AMV). Similarly, part of the 5 0 -UTR and the 5 0 most proximal part of MP of Peanut stunt virus were predicted to be donated by PNRSV.…”
Section: Introductionmentioning
confidence: 96%